Towards Detection of Redshifted 21-cm Signal from Cosmic Dawn and Epoch of Reionisation - Thekkeppattu, Jishnu Nambissan (Curtin University, 2022)
The redshifted 21-cm signal from neutral hydrogen has the potential to provide valuable information on the the periods of cosmic dawn and epoch of reionisation (CD/EoR). The sky-averaged or global component of the 21-cm signal is expected to be observable as a distortion to the low frequency radio spectrum. This thesis is on experimental techniques to detect the global 21-cm signal. Instrument descriptions, laboratory analysis, calibration and data analysis methods for two different instruments - SARAS-3 and SITARA - are provided. Advantages and challenges associated with each instrument are also discussed.